Fertility-related knowledge and information-seeking behaviour among people of reproductive age: a qualitative study. (3rd April 2017) - Hammarberg, Karin; Zosel, Rebecca; Comoy, Caroline; Robertson, Sarah; Holden, Carol; Deeks, Mandy; Johnson, Louise
Abstract: Some potentially modifiable factors adversely affect fertility and pregnancy health. To inform a fertility health promotion programme, this study investigated fertility knowledge and information-seeking behaviour among people of reproductive age. This was a qualitative study involving six focus group discussions with women and men who intended to have children in the future and eight paired interviews with couples who were actively trying to conceive. Participants ( n  = 74) themselves generally claimed 'low' to 'average' levels of knowledge about fertility. Most of them overestimated women's reproductive lifespan and had limited knowledge about the 'fertile window' of the menstrual cycle. The Internet was a common source of fertility-related information and social media was viewed as a potential effective avenue for dissemination of messages about fertility and how to protect it. Most participants agreed that primary health care providers, such as general practitioners (GPs), are well placed to provide information regarding fertility and pregnancy health. This study identified several gaps in knowledge among people of reproductive age about factors that influence fertility and pregnancy health negatively. Addressing these knowledge gaps in school curricula, primary care and health promotion would assist people to realize their reproductive goals and reduce the risk of infertility and adverse obstetric outcomes.